Phonological Errors in Reciting the Quran among Madrasah Diniyyah Students: Identifying Sources and Solutions | Al-Akhthā Al-Shauthiyyah fī Qirāah Al-Qurān Al-Karīm lada Thullāb Al-Madāris Al-Dīniyyah: Tahdīd Al-Mashādir Wa Al-Hulūl - Wahyudin, Dedih; Karim, Agus; Solehah, Mirna (UIN Sunan Gunung Djati Bandung, 2024)
The purposes of this research are to identify phonological errors among students and the sources of these problems, as well as to find solutions to address these errors in Quranic reading among second-grade students at Madrasah Diniyyah Miftahus-Sholihin. Many students are unable to read the Quran correctly. This phenomenon is influenced by various factors, such as the pronunciation of different letters between Arabic and Indonesian languages. The method used is qualitative through descriptive analysis. Data collection methods include observation, interviews, testing, and documentation. The results of this research show that the qiraah al-tahqiq method helps improve Quranic reading among students.This can be seen from the results of the first and second tests. In the first test, students' phonological errors amounted to 1055 errors. While in the second test, students' phonological errors amounted to 197 errors. These findings have important implications for Arabic language learning, particularly in the context of learning tajweed and correct pronunciation of Arabic letters. It suggests that a structured approach and a focus on phonological errors can improve Arabic language teaching in school. For further research, it is recommended to expand this study with a larger sample and different grade levels to obtain a more comprehensive picture of phonological errors and the effectiveness of learning methods.